Patterns of Recruitment and Induction in Selected European Countries : First Results of Feasibility Study - Grollmann, Philipp [Verfasser]; Geiben, Marthe [Verfasser] (My University, 2012)
The projects (Patterns of Recruitment and Induction in Selected European Countries, INDUCT II) described in this contribution "deal with an international comparison on the question of how companies recruit, with a focus on labour market entrants and what they (need to) do in order to make sure that labour market entrants fulfill the expectations that employers have in terms of skills and competences on the level of intermediate skilled work. One project was a feasibility study and the other project, that is just starting, is a full study following the feasibility study. The aim of the two projects was to investigate the linkage between establishments' recruitment practices, induction and work organization in various European countries and the quality assigned to such VET system by employers. "(Textauszug; BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; S 5.3 Personalentwicklung; I 2.2 Europa; Berufseinmündung; Zweite Schwelle; Betrieb; Personalgewinnung; Mittlere Qualifikation; Einarbeitung; Europa